Two-Dimensional Generalized Moment Representations and Padé Approximations for Some Humbert Series - Holub, A. P.; Chernetska, L. O. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
By extending Dzyadyk’s method of generalized moment representations to the case of two-dimensional number sequences, we construct and study Padé approximants for some confluent Humbert hypergeometric series.